2010
DOI: 10.1111/j.1399-0012.2010.01280.x
|View full text |Cite
|
Sign up to set email alerts
|

A case of second renal transplantation with acute antibody‐mediated rejection complicated with BK virus nephropathy

Abstract: Atsumi H, Asaka M, Kimura S, Imura J, Fujimoto K, Chikazawa Y, Nakagawa M, Okuyama H, Yamaya H, Moriyama M, Tanaka T, Suzuki K, Yokoyama H. A case of second renal transplantation with acute antibody‐mediated rejection complicated with BK virus nephropathy.
Clin Transplant 2010: 24 (Suppl. 22): 35–38. © 2010 John Wiley & Sons A/S. Abstract:  We reported a 40‐year‐old female case of second renal transplantation with antibody‐mediated rejection (AMR) complicated by BK virus nephropathy. She started hemodialysis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 7 publications
(9 reference statements)
1
9
0
Order By: Relevance
“…These observations are supported by previous case reports and series that examined concomitant C4d and BK staining in renal transplant recipients (21,22,28). Honsova et al (28) reported BKVN and focally positive C4d in 9/12 needle biopsy samples and 2 nephrectomy samples and noted that the ptc vascular endothelium posed a potential target for antibody response after injury from BKPyV infection.…”
Section: Discussionsupporting
confidence: 89%
“…These observations are supported by previous case reports and series that examined concomitant C4d and BK staining in renal transplant recipients (21,22,28). Honsova et al (28) reported BKVN and focally positive C4d in 9/12 needle biopsy samples and 2 nephrectomy samples and noted that the ptc vascular endothelium posed a potential target for antibody response after injury from BKPyV infection.…”
Section: Discussionsupporting
confidence: 89%
“…The appearance of IEL and interstitial inflammation are not specific for resolving PyVAN, and in our opinion the distinction of concurrent ICR is currently impossible. The main arguments for resolving PyVAN in our cohort are (1) PyVAN and acute rejection may not be mutually exclusive as concurrent vascular and/or antibody-mediated rejection has been reported in the literature in humans (28)(29)(30)(31)(32) as well as in a mouse models of BKV (33). It is interesting to note that patients with BKV viruria in the absence of viremia have a mild increase in the number of putative episodes of T-cell-mediated rejection (34,35).…”
Section: Discussionmentioning
confidence: 87%
“…The main arguments for resolving PyVAN in our cohort are (1) PyVAN and acute rejection may not be mutually exclusive as concurrent vascular and/or antibody-mediated rejection has been reported in the literature in humans (28)(29)(30)(31)(32) as well as in a mouse models of BKV (33). The main arguments for resolving PyVAN in our cohort are (1) PyVAN and acute rejection may not be mutually exclusive as concurrent vascular and/or antibody-mediated rejection has been reported in the literature in humans (28)(29)(30)(31)(32) as well as in a mouse models of BKV (33).…”
Section: Discussionmentioning
confidence: 96%
“…PyVAN and acute rejection may not be mutually exclusive as concurrent vascular and/or antibody‐mediated rejection has been reported in the literature in humans as well as in a mouse models of BKV . It is interesting to note that patients with BKV viruria in the absence of viremia have a mild increase in the number of putative episodes of T‐cell‐mediated rejection .…”
Section: Discussionmentioning
confidence: 91%